Definancialising well-being: the case of housing - Santos, Ana C. (2016)
This paper initiates discussion on how relevant areas of provision can be definancialised to combat inequities and uncertainties generated by financialisation. It does so by examining the housing system of provision as this is a domain that has contributed to households’ increasing involvement with financial markets, and finance’s expansion into adjacent domains of economic and social life. As analysis of the impact of financialisation and financial crisis required examining the ways in which finance interacts with the entire chain of production that forms a given system of provision, which is commodity-specific and is shaped by multiple factors, the examination of the definancialisation of housing likewise demands investigating the structures, agents, relations and processes that form a given housing system of provision in its social, political, geographical and historical context. A first step in this direction is attempted in this paper, mobilising, without being comprehensive, what we have learned about the embroilments of finance with the UK and the Portuguese housing systems of provision, and ongoing policy discussions in these two countries. The UK and Portugal comparison reveals relevant as these countries have highly financialised housing systems that are distinct enough to allow for contextual differentiation.